Ozone Sensitivity in Hybrid Poplar Is Correlated with a Lack of Defense-Gene Activation - Riehl Koch, Jennifer (American Society of Plant Physiologists, 1998)
Ozone is a major gaseous pollutant thought to contribute to forest decline. Although the physiological and morphological responses of forest trees to ozone have been well characterized, little is known about the molecular basis for these responses. Our studies compared the response to ozone of ozone-sensitive and ozone-tolerant clones of hybrid poplar (Populus maximowizii × Populus trichocarpa) at the physiological and molecular levels. Gas-exchange analyses demonstrated clear differences between the ozone-sensitive clone 388 and the ozone-tolerant clone 245. Although ozone induced a decrease in photosynthetic rate and stomatal conductance in both clones, the magnitude of the decrease in stomatal conductance was significantly greater in the ozone-tolerant clone. RNA-blot analysis established that ozone-induced mRNA levels for phenylalanine ammonia-lyase, O-methyltransferase, a pathogenesis-related protein, and a wound-inducible gene were significantly higher in the ozone-tolerant than in the ozone-sensitive plants. Wound- and pathogen-induced levels of these mRNAs were also higher in the ozone-tolerant compared with the ozone-sensitive plants. The different physiological and molecular responses to ozone exposure exhibited by clones 245 and 388 suggest that ozone tolerance involves the activation of salicylic-acid- and jasmonic-acid-mediated signaling pathways, which may be important in triggering defense responses against oxidative stress.